Early identification and awareness of child abuse and neglect among physicians and teachers - M. Roeders; J. Pauschek; R. Lehbrink; L. Schlicht; S. Jeschke; M.P. Neininger; A. Bertsche (BMC, 2024)
Abstract Background Child abuse and neglect (CAN) causes enormous suffering for those affected. Objective The study investigated the current state of knowledge concerning the recognition of CAN and protocols for suspected cases amongst physicians and teachers. Methods In a pilot study conducted in Mecklenburg-Western Pomerania from May 2020 to June 2021, we invited teachers and physicians working with children to complete an online questionnaire containing mainly multiple-choice-questions. Results In total, 45 physicians and 57 teachers responded. Altogether, 84% of physicians and 44% of teachers were aware of cases in which CAN had occurred in the context of their professional activity. Further, 31% of physicians and 23% of teachers stated that specific instructions on CAN did not exist in their professional institution or that they were not aware of them. All physicians and 98% of teachers were in favor of mandatory training on CAN for pediatric residents and trainee teachers. Although 13% of physicians and 49% of teachers considered a discussion of a suspected case of CAN to constitute a breach of confidentiality, 87% of physicians and 60% of teachers stated that they would discuss a suspected case with colleagues. Conclusion Despite the fact that a large proportion of respondents had already been confronted with suspected cases of CAN, further guidelines for reporting procedures and training seem necessary. There is still uncertainty in both professions on dealing with cases of suspected CAN.